2020
DOI: 10.3168/jds.2019-17827
|View full text |Cite
|
Sign up to set email alerts
|

Development of a quantitative risk assessment of bovine viral diarrhea virus and bovine herpesvirus-1 introduction in dairy cattle herds to improve biosecurity

Abstract: A quantitative risk assessment model was developed to estimate the annual probability of introducing bovine viral diarrhea virus (BVDV) and bovine herpesvirus 1 (BoHV-1) at the farm level through animal movements. Data from 2017 official animal movements, biosecurity questionnaires, scientific literature, and expert opinion from field veterinarians were taken into consideration for model input parameters. Purchasing or introducing cattle, rearing replacement heifers offsite, showing cattle at competitions, sha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 56 publications
0
13
0
Order By: Relevance
“…Likewise, the grazing lease was established as a risk factor for the presentation of BVD in Sotaquirá town; possibly due to farm laborer's that implement management practices or transport animals from one grassland to another are exposed to other herds, which increases the risk of contagion by direct contact with infected animals or with contaminated surfaces, becoming a relevant factor on the transmission of the virus. However, it is important to clarify that transportation does not necessarily result in all cattle being infected by BVDV seropositive animals ( Benavides et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, the grazing lease was established as a risk factor for the presentation of BVD in Sotaquirá town; possibly due to farm laborer's that implement management practices or transport animals from one grassland to another are exposed to other herds, which increases the risk of contagion by direct contact with infected animals or with contaminated surfaces, becoming a relevant factor on the transmission of the virus. However, it is important to clarify that transportation does not necessarily result in all cattle being infected by BVDV seropositive animals ( Benavides et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, beef cattle underwent a long travel from France to Italy (Veneto region) and a process of mixing both before travelling and at arrival to the fattening farms. Currin and Whittie [ 29 ] reported that transportation, especially during cross-country travels, is a stressful event for the animals, and Benavides et al [ 30 ] reported higher likelihood of cross-contamination among animals for bovine viral diarrhea virus when farms shared transport vehicles or animals were transferred in contaminated vehicles. The aforesaid stressful events combined to the process of adaptation to a new farm environment can increase animals’ susceptibility to diseases (e.g., BRD and bovine viral diarrhea virus) which in turn may affect their performance [ 25 , 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…This was highlighted by the European Commission's Animal Health Strategy for the European Union (2007-2013), which focused on "prevention is better than cure" (29). Previous studies have suggested that the probability of introducing BVDV and BoHV-1 could be reduced by the implementation of biosecurity measures (30). However, limited information is available on the biosecurity practices within Irish farms.…”
Section: Discussionmentioning
confidence: 99%